Development of driving assistant system for smart vehicle from series of image sequence - Muad, Anuar Mikdad; Hussain, Aini (Penerbit Universiti Sains Malaysia, 2004)
An autonomous intelligent vehicle system that can interpret traffics situation, provides driving assistance and capable of avoiding collisions can significantly increased driving safety. Such a vehicle system will have to perform several functionalities. In this work, a visual based sensor is used to acquire information by placing a web-camera at the dashboard of a moving car and directed outward in a way to have a similar view with a real driver. The camera captures image sequences where every frame of image provides information pertaining to road and traffic situations.